Cyclooxygenase-2 (Cox-2) in injured human nerve and a rat model of nerve injury. - Durrenberger, P; Facer, P; Gray, R; Chessell, I; Naylor, A; Bountra, C; Banati, R; Birch, R; Anand, P (2004)
Inflammation associated with nerve injury produces a number of pathogenic chemical mediators of which prostanoids are a potent component. Cyclooxygenases (Cox-1 and Cox-2) are the enzymes responsible for prostanoid production. We have investigated Cox-2 immunoreactivity (Cox-2-IR) and glial activation in human injured (n = 16) and uninjured (n = 8) nerves and in the chronic constriction injury (CCI) model of nerve injury in the rat, using immunohistological and autoradiographic methods. Tissues were immunostained with antibodies to Cox-2, CD-68 (human macrophage marker), OX42 (rat microglial marker), or incubated with tritiated PK11195 (marker of glial activation), prior to image analysis. In human nerves, Cox-2-IR was detected in cells with morphology and distribution similar to macrophages/microglia - these were increased significantly in human nerve proximal to injury (p < 0.002), reaching a peak at 4-6 weeks after injury. In the rat CCI model, at 40 days after injury, microglia-like cells with Cox-2-IR were increased significantly in the injured nerve (p < 0.004) and ipsilateral dorsal spinal cord (p < 0.008). PK11195-binding results were similar for Cox-2-IR in chronic injured human nerve and rat tissues. These findings suggest that Cox-2-immunoreactive cells could play a role in processes associated with Wallerian degeneration, nerve regeneration, and the development of persistent pain. Selection of patients 4-6 weeks after nerve injury would be more likely to show any efficacy of Cox-2 inhibitors.